DESAIN BAHAN AJAR DIGITAL BERBASIS GENIALLY PADA MATA PELAJARAN IPAS: STUDI PADA MATERI ALAT GERAK MANUSIA UNTUK FASE C - Dewi, Santi Kurnia; Suciptaningsih, Oktaviani Adhi; Mas’ula, Siti (STKIP Persada Khatulistiwa Sintang, 2025)
In the context of the Merdeka Curriculum, Natural and Social Sciences (IPAS) learning not only serves to transmit knowledge but also fosters students’ critical and creative thinking skills through contextual and experiential approaches. One of the key topics in IPAS for Phase C, particularly in sixth grade, is the human movement organs, which integrates an understanding of body structure, physiological functions, and healthy lifestyle habits. However, the main problem encountered is students’ limited understanding of movement organs and their functions, as reflected in the average scores that remain below the minimum mastery criteria. This issue arises from the limited instructional media used by teachers to explain abstract concepts. This study aims to design digital teaching materials based on Genially for the IPAS subject on human movement organs for sixth-grade students. The research employed a qualitative descriptive approach involving teachers and sixth-grade students at an elementary school in Pasrepan District. Data were collected through observation, interviews, and documentation, and validated using source and technique triangulation. Data analysis included data reduction, data display, and conclusion drawing. The results showed that the use of Genially-based digital materials enhanced student engagement, improved conceptual understanding of human movement organs, and provided an interactive and enjoyable learning experience.